Clinical challenges of a co-secreting TSH/GH pituitary adenoma. (17th September 2019) - Ng, Hui Yi; Namboodiri, Divya; Learoyd, Diana; Davidson, Andrew; Champion, Bernard; Preda, Veronica
Abstract : Summary: Co-secreting thyrotropin/growth hormone (GH) pituitary adenomas are rare; their clinical presentation and long-term management are challenging. There is also a paucity of long-term data. Due to the cell of origin, these can behave as aggressive tumours. We report a case of a pituitary plurihormonal pit-1-derived macroadenoma, with overt clinical hyperthyroidism and minimal GH excess symptoms. The diagnosis was confirmed by pathology showing elevated thyroid and GH axes with failure of physiological GH suppression, elevated pituitary glycoprotein hormone alpha subunit (αGSU) and macroadenoma on imaging. Pre-operatively the patient was rendered euthyroid with carbimazole and underwent successful transphenoidal adenomectomy (TSA) with surgical cure. Histopathology displayed an elevated Ki-67 of 5.2%, necessitating long-term follow-up. Learning points: Thyrotropinomas are rare and likely under-diagnosed due to under-recognition of secondary hyperthyroidism. Thyrotropinomas and other plurihormonal pit-1-derived adenomas are more aggressive adenomas according to WHO guidelines. Co-secretion occurs in 30% of thyrotropinomas, requiring diligent investigation and long-term follow-up of complications.